Avaliações online de produtos: o efeito da fonte de informação na confiança do consumidor - Schunck, Josiane Garcelli (2023)
With the growth of e-commerce, the interest of consumers in seeking information and evaluations of products and services on the Internet before making their purchases has been remarkable. Economic concepts defend that the search for information before purchase can be analyzed from a cost-benefit structure, while the source credibility theory shows that the greater the confidence in the source of information, the greater the impact on the customer's decision. Knowing the importance of online reviews, some companies have monetarily incentivized authors to write biased or fake reviews. Therefore, the purpose of this study was to understand whether the distinct types of information sources in an online product review affect customer confidence and online behavior, and whether the fact that the source is paid or not to conduct the review influences perceptions. and consumer decisions. Four studies were conducted, two in the laboratory and two in the field. The experiments concluded that the diverse sources of information evaluated here, that is, experts, consumers, or virtual assistants, exert different influences on consumer trust. Trust was measured in its three dimensions: competence, benevolence and integrity, and the laboratory study with 185 respondents pointed to the specialist as the most reliable source in the three dimensions. The field study accessed 12,000 customers in real situations on a review site and complemented the finding, pointing out that the most trusted source also generated higher click-through rates and lower bounce rates on the review site. The second laboratory study indicated that if the expert is paid, he is seen as more competent, although less benevolent. The same study was replicated in a field experiment and the click-through rate was higher on the site where the expert was not paid to perform the assessments. The main contribution of this work was to compare the trust level of three types of sources in the same study and to be able to relate the results with real customer behavior on the review website. This information is valuable for the literature of online product reviews and for marketing professionals, in the online environment, who can work to offer reliable information to their customers and help them in decision making.